Can self-regulatory strength training counter prior mental exertion? a systematic review of randomized controlled trials - Sun, He; Soh, Kim Geok; Norjali Wazir, Mohd Rozilee Wazir; Ding, Cong; Xu, Tingting; Zhang, Dong (Frontiers Media, 2022)
Background: Prior mental exertion consumes self-regulation and influences any subsequent physical or cognitive performance according to the strength model of self-regulation. However, the counteractive effect of self-regulatory strength training remains unclear. Objective: This study aims to report a comprehensive systematic review investigating self-regulatory strength training programmes on physical or cognitive performance. Methods: To select relevant studies from the available literature, a thorough search was conducted on PubMed, Web of Science, EBSCOhost (CENTRAL, Psychology and Behavioral Sciences Collection, SPORTDicus), Scopus, and Google Scholar, as well as the sources of reference for gray literature. Only randomized controlled trials involving healthy humans, strength-based self-regulation training programmes with comparable protocols, and a physical or cognitive task associated with the study were selected for the current review. The Grading of Recommendations Assessment Development and Evaluation (GRADE) framework was used to develop the summary of findings. Results: Twelve articles were included based on the selection criteria. Evidence certainty for outcomes was graded as either low or very low level. The majority of the studies reported that self-regulatory strength training programmes can significantly counter prior mental exertion and decrement of performance, while only one study did not find such improvement. According to the strength model, a period of training increased the ‘self-regulatory muscle.' Conclusion: Strength is an important ingredient in the resource model of self-regulation and can be trained to counter prior mental exertion and improve subsequent physical and cognitive performance. The training effects are cross-domain (e.g., emotional and cognitive domains; higher and lower levels of executive functions). However, motivation plays a key role to mobilize this resource. Future studies should examine the mechanism that underlies the strength.